Decolonising the curriculum: Perspectives from the Global South - Knowles, Rachel (2022)
In this review we offer a series of reviews and commentaries on articles from Nepal, Argentina and Australia addressing different issues relating to the decolonisation of curricula and academic methodologies, research and history.